Benefits of non-work interactions with your supervisor: Exploring the bottom-up effect of employee boundary blurring behavior on abusive supervision - Jiang, Luyuan; He, Guohua; Zhou, Hansen; Yang, Laijie; Li, Xiaolan; Li, Wenpu; Qin, Xin (Frontiers in Psychology, 2022)
Abusive supervision has long been found to have remarkably negative impacts on individual and organizational outcomes. Accordingly, prior studies have explored many organizational and supervisor-related predictors of abusive supervision and offered several interventions to reduce it. However, extant research lacks the bottom-up perspective to explore how employees can act to reduce abusive supervision. Drawing on self-disclosure theory, we develop and test a model of whether and how employee boundary blurring behavior may protect them from being abused by their supervisors. Specifically, we test the model in a scenario-based experiment and a multi-source, multi-wave field study. The results reveal a negative indirect effect of employee boundary blurring behavior on abusive supervision via supervisor liking toward the employee. By uncovering employee boundary blurring behavior as an antecedent of abusive supervision, we enrich the abusive supervision literature with a bottom-up behavioral strategy for employees to proactively protect themselves from being abused.